Foraging activity of africanized honeybees (Apis mellifera L.): A study of nectar and pollen resources on a temporal scale - Polatto, Leandro Pereira; Alves Junior, Valter Vieira; Dutra, João Cloves Stanzani; Chaud-Netto, José (EntomoBrasilis, 2019)
Abstract. The spatial and temporal distribution of food resources, as well as the type, quantity, and quality of the foods stocked in the hive are the principal regulatory factors of the choice and intensity of floral resource harvesting by bees. We evaluated the annual foraging activity of Africanized honeybees Apis mellifera L. (Apidae) on the most abundant natural food resources available. Nineteen abundant plant species susceptible to foraging by bee communities in the interior of a secondary growth forest fragment with a transition physiognomy between Atlantic Forest and Cerradão vegetation were accompanied to estimate the intensity of floral resource collection by Africanized honeybees A. mellifera during the year. We determined the productivity of the flowers (the quality and quantity of nectar and/or pollen made available) and floral abundance (the quantities of flowers produced and the duration of flowering) of the 19 plant species selected. Africanized honeybees A. mellifera collected floral resources from 11 species. The intensities of visits per flower and per area of floral exposition were greater among plant species visited by Africanized honeybees when bee collecting behavior resulted in pollen transfer to the floral stigmas. It is estimated that 70.5% of all visits by Africanized honeybees A. mellifera individuals during the year in the study area occurred on Senegalia polyphylla (DC.) Britton & Rose (Fabaceae), Grazielia cf. dimorpholepis (Baker) R.M.King & H.Rob (Asteraceae), and Gouania cf. latifolia Reissek (Rhaminaceae); those visits demonstrated seasonal patterns, with peaks of activity between January and April. Weak foraging activity was observed in June and between June and November. Atividade de forrageio de abelhas africanizadas (Apis mellifera L.): um estudo das fontes de néctar e pólen em uma escala temporal Resumo. A distribuição espacial e temporal dos recursos alimentares, bem como o tipo, quantidade e qualidade do alimento estocado na colmeia são os principais fatores reguladores na escolha e intensidade da coleta dos recursos florais pelas abelhas. O objetivo desse trabalho foi avaliar a atividade anual de forrageio de abelhas africanizadas Apis mellifera L. (Apidae) nas fontes alimentares naturais mais abundantes. A coleta de dados foi realizada em 19 espécies vegetais abundantes e suscetíveis ao forrageio pela comunidade de abelhas no interior de um fragmento de floresta secundária com fisionomia em transição entre Mata Atlântica e Cerradão, durante um ano. Para estimar a intensidade de coleta de recursos florais pelas abelhas africanizadas A. mellifera, foi determinada a produtividade das flores (qualidade e quantidade do néctar e/ou pólen alocada nas flores) e a abundância (quantidade de flores e duração do florescimento) das 19 espécies vegetais selecionadas. As abelhas africanizadas A. mellifera coletaram recursos florais em 11 espécies vegetais. As intensidades de visitas por flor e áreas de exposição floral foram superior nas espécies de plantas que foram visitadas pelas abelhas africanizadas A. mellifera cujos comportamentos de coleta resultavam em transferência de pólen aos estigmas das flores. Estima-se que 70,5% de todas as visitas promovidas por A. mellifera africanizada no decorrer do ano na região de estudo ocorreram em Senegalia polyphylla (DC.) Britton & Rose (Fabaceae), Grazielia cf. dimorpholepis (Baker) R.M.King & H.Rob (Asteraceae), e Gouania cf. latifolia Reissek (Rhaminaceae), demonstrando, dessa forma, um padrão sazonal, com picos de atividade em janeiro, abril e agosto, respectivamente. Por outro lado, houve fraca atividade de forrageio em junho e entre setembro e novembro.